Effects of Nb and Mo on the microstructure and properties of 420 stainless steel processed by laser-powder bed fusion - GÜLSOY, HAMİT ÖZKAN (ELSEVIER, 2019)
Niobium (Nb) and molybdenum (Mo) are conventionally added to stainless steels to improve their mechanical and corrosion properties. However, the effects of Nb and Mo addition on the processing and properties in laser-powder bed fusion (L-PBF) have not been well investigated, especially in the context of 420 stainless steel. In this study, 420 stainless steel pre-alloyed with Nb (1.2 wt.%) and Mo (0.57 wt.%) was processed by L-PBF and characterized in terms of its physical, mechanical and corrosion properties as well as microstructure. The addition of Nb and Mo did not significantly affect the densification of 420 stainless steel when printed over an energy range of 28-75 J/mm(3) and a maximum density of 99.3 +/- 0.02% theoretical at 63 J/mm(3) was achieved. In mechanical tests, L-PBF 420 stainless steel specimens exhibited higher mechanical properties in the presence of Nb and Mo. After heat treatment, the UTS of 420 stainless steel with Nb and Mo improved to 1750 +/- 30 MPa and elongation to 9.0 +/- 0.2%, much higher than previously reported properties achieved in L-PBF and exceeding wrought 420 stainless steel. The tempering of martensite phases as well as the presence of nanoscale NbC were found to correlate with improved mechanical properties. In electrochemical tests, 420 stainless steel exhibited slightly better corrosion properties with the addition of Nb and Mo.
Keywords: Laser-powder bed fusion; 420 Stainless steel; Niobium; Tensile strength; Microstructure; MECHANICAL-PROPERTIES; PROCESS PARAMETERS; CORROSION PROPERTIES; RETAINED AUSTENITE; NIOBIUM; TITANIUM; PRECIPITATION; BEHAVIOR; TEMPERATURE; SIMULATION